Scientific - innovative methods of teaching the subject of life safety in the Republic of Uzbekistan - Yuldashev Orunbai Rakhmonberdievich; Abdurakhmanova Sayyorakhon Ruzalievna (Zien Journals, 2022)
The article deals with the issues of modern scientificdevelopment of an integrated management system for life safety and social insurance in the context of transition to a market model of economic development.
Keywords: Safety; labor protection; management; systematic approach